PENGARUH PENDEKATAN PEMBELAJARAN DAN KREATIVITAS TERHADAP PEMAHAMAN KONSEP IPA DI SEKOLAH DASAR - Zulafni, Zulafni; Asrial, Asrial; Yamin, Martinis (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
Learning approach is the starting point or point of view of the learning process, because it is necessary to design an interactive learning process, inspiring, fun, challenging, and motivating learners to actively participate and provide enough space for innovation, creativity, and independence in accordance with flair , interests, and physical and psychological development of learners. This study was a quasi-experimental study. Analysis of the data used is the analysis of variance (ANOVA) and two lanes. The purpose of research to determine: 1) The difference between the students understanding of science concepts are learned with PKP-MD with students who learned with PK-ME, 2) Differences in understanding science concepts among students who have high creativity with students who have low creativity, 3) Difference understanding of science concepts among students who choose a high creativity that learned with PKP-MD with students who have high creativity learned with PK-ME, 4) differences between students understanding of science concepts, who has a low creativity that learned with PKP-MD with students who have low creativity learned with PK-ME, 5) interaction using PKP-MD and PK-ME with creativity to the understanding of science concepts. The results showed the following findings: 1) Understanding the concept of science students who learned with PKP-MD different from the students who learned with PK-ME, 2) understanding the concept of science students who have high creativity differently than students who have low creativity, 3 ) Understanding the concept of science students who have high creativity learned with PKP-MD differ from students who have high creativity learned with PK-ME, 4) Understanding the concept of science students who have low creativity learned with PKP-MD is relatively the same as students who have low creativity learned with PK-ME, 5) There is no significant interaction between the use of PFM-MD and PK-ME with creativity to the understanding of science concepts. Keywords : learning approach, creativity, understanding of concepts